Point prevalence surveys of health-care-associated infections: a systematic review. (19th May 2019) - Saleem, Zikria; Godman, Brian; Hassali, Mohamed Azmi; Hashmi, Furqan Khurshid; Azhar, Faiza; Rehman, Inayat Ur
ABSTRACT: Health-care-associated infections (HAIs) are considered a serious public health issues that contribute substantially to the global burden of mortality and morbidity with respect to infectious diseases. The aim is to assess the burden of health-care-associated infections by collation of available data from published point prevalence surveys (PPS) on HAIs to give future guidance. Study protocol and methodology were designed according to preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines. Published research papers that conducted a point prevalence survey of HAIs in hospital settings by following the structured survey methodology employed by European Centre of Disease Prevention and Control (ECDC) were included. Of 1212 articles, 67 studies were included in the final analysis conducted across different countries. Overall, 35 studies were conducted in Europe, 21 in Asia, 9 in America, and 2 in Africa. The highest prevalence of HAIs was recorded in a study conducted in adult ICU settings of 75 regions of Europe (51.3%). The majority of the studies included HAI data on urinary tract infections, respiratory tract infections, and bloodstream infections. Klebsiella pneumonia, Pseudomonas aeruginosa and E. coli were the most frequent pathogens responsible for HAIs. PPS is an useful tool to quantify HAIs and provides a robust baseline data for policymakers. However, a standardize surveillance method is required. In order to minimize the burden of HAIs, infection prevention and control programs and antibiotic stewardship may be effective strategies to minimize the risk of HAIs.